2014
DOI: 10.1093/ejcts/ezu243
|View full text |Cite
|
Sign up to set email alerts
|

Multiple factors predict the risk of spinal cord injury after the frozen elephant trunk technique for extended thoracic aortic disease

Abstract: There were multiple factors predicting the risk of SCI after the FET technique. Paraplegia may be prevented by avoiding deep insertion of the stent graft and by keeping blood pressure elevated after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 19 publications
1
73
0
1
Order By: Relevance
“…Sizing of the endograft for the hybrid approach is crucial because the endograft needs to be large enough to open up the collapsed true lumen and avoid type I endoleak. But, in the meantime, oversizing would cause SINE (33). SINE can cause catastrophic complication after hybrid type A dissection repair (17,24).…”
Section: Sizing Techniquementioning
confidence: 99%
“…Sizing of the endograft for the hybrid approach is crucial because the endograft needs to be large enough to open up the collapsed true lumen and avoid type I endoleak. But, in the meantime, oversizing would cause SINE (33). SINE can cause catastrophic complication after hybrid type A dissection repair (17,24).…”
Section: Sizing Techniquementioning
confidence: 99%
“…Conversely, an overly deep implantation of a FET can lead to spinal cord injury. 2,3) The incidence of spinal cord injury following the FET technique ranges between 3.5% and 24%. [2][3][4] A distal landing zone over T7 has been reported as an independent risk factor for spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) The incidence of spinal cord injury following the FET technique ranges between 3.5% and 24%. [2][3][4] A distal landing zone over T7 has been reported as an independent risk factor for spinal cord injury. 3) The simplest method for the positioning of a FET is marking the preoperatively measured length on the stent graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-hospital mortality (10%) and stroke (4.8%) rates were extremely satisfactory while the risk of spinal cord injury (4.3%) appeared to be higher than that reported in more conservatively managed series. In this setting, lately, Katayama et al showed that in patients undergoing FET, postoperative spinal cord injury may be prevented or minimized by avoiding deep insertion of the stent graft, keeping blood pressure elevated after the operation and using cerebrospinal fluid drainage (40). Nevertheless, the spinal cord injury remains the main Achilles heel of FET procedure.…”
Section: Current Evidencementioning
confidence: 99%